2020
DOI: 10.22363/2312-797x-2020-15-1-30-39
|View full text |Cite
|
Sign up to set email alerts
|

Effect of humic acid and naphthalene acetic acid on vegetative growth and fruit quality of tomato plants Lycopersicon esculentum

Abstract: The study aimed to improve fruit set and plant performance to increase tomato productivity by studying the effect of plant growth regulators on tomato plants (Lycopersicon esculentum). A specific experiment has been carried out to study the effect of plant growth regulators Hemo bles (humic acid, 850g/kg) at applied doses (250, 500 and 700 ppm) and Magictone (naphthalene acetic acid and naphthalene acetamide, 5…12.5 g/kg) at applied doses (250, 500 and 700 ppm) on growth and physiological characteristics of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 5 publications
(6 reference statements)
0
0
0
Order By: Relevance
“…Our results showed that the protein and carbohydrate levels increased with two levels of HA application across all composts (Table 10). Numerous studies have discussed the significant effects of HA on carbohydrate and protein content in various plant roots, including ginger rhizomes [Taibo et al, 2007], tomato [Suliman et al, 2020;Lu et al 2023], turnip roots [Aisha et al, 2014], and radish [Barzegar et al, 2021], which are corroborated by our findings. Ma et al (2022) demonstrated that HA treatment significantly improves soil health parameters, which may have affected the absorption of macro-elements.…”
Section: Discussionsupporting
confidence: 89%
“…Our results showed that the protein and carbohydrate levels increased with two levels of HA application across all composts (Table 10). Numerous studies have discussed the significant effects of HA on carbohydrate and protein content in various plant roots, including ginger rhizomes [Taibo et al, 2007], tomato [Suliman et al, 2020;Lu et al 2023], turnip roots [Aisha et al, 2014], and radish [Barzegar et al, 2021], which are corroborated by our findings. Ma et al (2022) demonstrated that HA treatment significantly improves soil health parameters, which may have affected the absorption of macro-elements.…”
Section: Discussionsupporting
confidence: 89%